Strategi Radio Bintang Tenggara 95,6 FM Banyuwangi melalui Program Jumat Berkah dalam Mempertahankan Eksistensinya di Tengah Konvergensi Media Online - Siti Muflihatur Rohmah; Minan Jauhari (Fakultas Dakwah Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2022)
The development of technology and information is significant, triggering competition between a media to seize its position. One of them is radio media. In the current era of media convergence, radio which is considered a traditional media must survive in the midst of online media convergence to maintain its existence as well as expand its audience and get advertisements. This happened at Bintang Tenggara Radio 95.6 FM, which is considered to have implemented the practice of online media convergence. This research is a qualitative descriptive study to describe the strategy of Radio Bintang Tenggara 95.6 FM through the Friday Blessing Program in maintaining its existence in the midst of online media convergence. Data collection techniques in this study were carried out using observations, interviews, and documentation owned by Radio Bintang Tenggara and then described the subject under study. The results of this study show that Radio Bintang Tenggara 95.6 FM Banyuwangi has strategies according to Susan Tyler Easmant's theory, including conformity strategies, habit formation strategies, listener flow control strategies, program storage strategies and mass attracting strategies. This strategy is used to maintain the existence of Radio Bintang Tenggara 95.6 FM through the Friday Blessing Program amidst the convergence of online media.